Patterns of Strategic Change in the Development of Human Resource Management - Pettigrew, A; Hendry, C (1992)
In addition to being characterized by the consistency of employment decisions one with another and their alignment with business strategy, human resource management (HRM) has also been deeply involved in the reshaping of organization structures in the 1980s, under conditions of increased external and internal complexity, and in managing other aspects of strategic change. These have contributed to the distinctive character of HRM and the shift away from a style of personnel management focused on administration and industrial relations. This evolution is explored through the concept of life-cycle change in a sample of ten firms that underwent major transformation during the 1980s.